PERAN KEPEMIMPINAN DALAM MENGEMBANGKAN LEMBAGA PELATIHAN KERJA (LPK) CEMERLANG TEKNIK KOTA BENGKULU - Sihombing, Arjun E.; Hutauruk, Lenni Mantili; Ulfasari, Nia (IKIP Siliwangi, 2025)
The purpose of this study is to describe the role of leadership in developing an excellent vocational training institution (LPK) in Bengkulu City. The research method used is a qualitative method with a descriptive approach. Data collection was carried out through interviews, observations, and documentation studies. The results of this study show the role of leadership in developing vocational training institutions in Bengkulu City. First, it describes the functions of leadership, namely the leader as the decision maker, as the spokesperson for the organization, as an effective communicator, as a mediator, and as an integrator. Second, it describes the characteristics of transformational leadership style, namely leaders who set an example, encourage subordinates' performance, harmonize the work environment, empower subordinates, and are able to deal with difficult situations. Third, it describes the main components of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. These components complement each other in forming an effective leadership style, encouraging followers to reach their maximum potential, creating an inspiring vision, encouraging creativity, and paying attention to individual needs and development on a personal level.